That was now, this is then - Williamson, Michael Z. (Baen, 2022)
Then: First Lieutenant Sean Elliott and nine other mixed-service U.S. soldiers on a convoy in Afghanistan suddenly found themselves and their MRAP vehicle thrown back to Earth's Paleolithic Age. And they were not alone. Displaced Romans, Neolithic Europeans, and more showed up as well. Some would be allies. Some became deadly foes. Now: Scientists from an almost unimaginably far future need the survivors' advice and support to reconnoiter and ultimately recover other groups displaced in time. The problem is not all of those other groups want to be recovered or even understand where they are. Prehistory is an ugly place, fascinating to visit, but no place for a civilized person to live. But the future, gorgeous as it is, has a darker side that dampens the appeal. In the end, only inventiveness, grit, and a thirst for freedom from the fickle tides of time can keep Sean and the displaced Americans alive and on a path to finally find a place-and a time-to call home.